PENGARUH CORPORATE GOVERNANCE DAN PROFITABILITAS TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - SE, Erika (Jurnal Ilmiah Mahasiswa FEB, 2017)
The study aims to reveal the influence of corporate governance and profitability on corporate social responsibility disclosure. The type of data used is secondary data. The population in this study is  manufacturing  company  basic  industry  and  chemical sector listed  in  the Indonesia Stocks Exchange  in 2014  and  2015. The sampling  method  used  is purposive sampling and obtained 114 sample. The data analysis method used in this study is multiple regression. The results of the study show that the mechanisms of corporate governance such as size board of commisioner and frequency o f board meeting have positive effect on the company’s  disclosure  upon  it’s  corporate  social  responsibility.  While  profitability  with Return on Assets as the proxy have negative effect on corporate social responsibility disclosure.  Meanwhile,  the  component  of  mechanisms  of corporate  governance  such  as independent board of commisioner, public shareholding and foreign ownership   does not affect the corporate social responsibility disclosure.Keyword: Corporate Governance, Profitability, Corporate Social Responsibility Disclosure